PENGARUH MEDIA PEMBELAJARAN KARTU APRESIASI TERHADAP HASIL BELAJAR SENI BUDAYA SUB BIDANG STUDI SENI RUPA SISWA KELAS VII SMP NEGERI 3 MANDAU - Mutia Devita, Dr. Ramalis Hakim, M.Pd., Drs. Wisdiarman, M.Pd. (Universitas Negeri Padang, 2018)
Study aimed to determine the effect of appreciation card media use the learning outcomes of arts and culture sub-field of study in art class VII SMP Negeri 3 Mandau. The hypothesis of study is there a difference between learning outcomes appreciation of art using instructional media appreciation card with learning outcomes using conventional media. Sampels were students of class VII with a number of 41 students between experimental class and control class. Research data was colleted by achievment test and data are the analyzed using the t test. This study shows that the use instructional media card and a good appreciation of the possitive effect in improving student learning outcomes in the field of fine arts.Keyword : Learning Media, Card Appreciation, Learning Outcomes and Art Study